Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan pada Satuan Kerja Seksi Keuangan Polres - Delvina Yulanda; Rosananda Oktala (IPM2KPE, 2021)
This study aimed to determine the effect of Human Resource (HR) Competence on the Quality of Financial Reports. This study used a sample of all employees at the Police Department of Finance. The data collection technique used in this study was to distribute questionnaires to 35 employees of the Police Department of Finance. Data were tested using classical assumption tests such as normality tests. The analysis technique used in this research is simple regression analysis, t-test, and the coefficient of determination (R2). The results of this study indicate that partially Human Resource (HR) Competence has a significant positive effect on the Quality of Financial Reports with a significance value of 0.000 <(Î± = 0.05) and the value of t count (9.148)> t table (1.692) which means Human Resource (HR) competence has a significant positive effect on the quality of financial reports. Keywords: Human Resources (HR) Competence, Quality of Financial Reports, Lahat Police Department of Finance